2013
DOI: 10.5455/2320-1770.ijrcog20130930
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic evaluation of tubal factor in cases of infertility

Abstract: Background: Tubal factor infertility accounts for approximately 25-35% of cases of female infertility. The evaluation of the fallopian tube is necessary to determine the management plan for infertility. Tubal patency can be diagnosed by hysterosalpingography (HSG) or laparoscopy with chromopertubation. The aim of this study was to determine the role of laparoscopy in the evaluation of tubal factor in infertile women. Methods: Fifty women presenting with complaints of primary and secondary infertility were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
23
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 8 publications
(6 reference statements)
9
23
2
Order By: Relevance
“…4 In another similar study Shetty SK et al showed endometriosis in 12 (24%) cases and peritubular adhesion in 4 (8%) cases where endometriosis was higher but adhesion was lower than our study. 5 Gulfarreen Haider et al observed endometriosis in 13 (43%) cases which was also higher than our study. 6 The higher rate of endometriosis may be due to delayed marriage, postponement of first conception and increased use of diagnostic laparoscopy.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…4 In another similar study Shetty SK et al showed endometriosis in 12 (24%) cases and peritubular adhesion in 4 (8%) cases where endometriosis was higher but adhesion was lower than our study. 5 Gulfarreen Haider et al observed endometriosis in 13 (43%) cases which was also higher than our study. 6 The higher rate of endometriosis may be due to delayed marriage, postponement of first conception and increased use of diagnostic laparoscopy.…”
Section: Discussioncontrasting
confidence: 52%
“…7 Another study done by Shetty SK et al show, bilateral tubal block in 8% and unilateral tubal block in 28% cases which were higher than our study. 5 Ikechebelu JI and Mbamara SU reported a higher…”
Section: Discussionmentioning
confidence: 99%
“…8 Tubal and peritoneal pathology account for infertility in 30-35% of the cases. 9 Most common hysteroscopic abnormality detected was septate uterus in primary infertility group (14.28%) ( Table 3). Uterine pathologies are responsible for 15% of infertility patients who seek treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However in a study by Mahmood et al, the incidence of endometriosis was 13.6%. 18 In the study of Shetty et al this incidence was 18.0% 8 and Aslam et al and asghar et al reported 25.0% incidence of endometriosis in their studies. 19,20 Our study supported the results of these studies.…”
Section: Discussionmentioning
confidence: 93%
“…7 Genital tuberculosis is also a cause of tubal blockage in developing countries like Pakistan, Bangladesh, India and Nepal. 8 Laparoscopy hysterosalpingography (HSG), and hystroscopy are techniques used to investigate tubal defects. Laparoscopy has a vital role in the diagnostic evaluation of women with infertility.…”
Section: Introductionmentioning
confidence: 99%